Hubungan Tingkat Pengetahuan, Sikap dan Tingkat Dukungan Keluarga dengan Praktik Perawatan Diri Pada Penderita Kusta di Kota Semarang - Hidayah, Elma Nur; Ginandjar, Praba; Martini, Martini; Udiyono, Ari (Jurnal Ilmiah Mahasiswa, 2020)
Title: The Correlation of Knowledge, Attitude and Family Support with Self-Care Practices in Patients of Leprosy in Semarang CityBackground: The proportion of disabilities of people affected by leprosy in Semarang from 2017 to 2018 increased from 21% to 26%.Â The national target for disability in leprosy has not yet reached (the target of 5%). Based on the results of a preliminary study of self-care practices, there are 50% of people affected by leprosy who are not good at self-care. The purpose of this study was to analyze the factors related to the practices of self-care in patient of leprosy in Semarang City.Methods: The design of this study was cross sectional. The subjects of this study were leprosy patients in Semarang city in 2016-2018 who were still doing self-care were 52 patients. The sampling method used is total sampling. The statistical test used was the chi-square test with a confidence level of 95%. Result: Statistical analysis showed that there was a correlation between knowledge (p = 0.006) and family participation (p = 0.012) with the practice of self-care practices in leprosy patients, while the attitude towards self-care (p = 0.052) proved to be no relationship. Conclusion: There is no relationship between the level of family support and self-care practices for people with leprosy.